Is there a Grammatical Comprehension Deficit in Multidomain Mild Cognitive Impairment? - López-Higes, Ramón; Departamento de Psicología Básica II (Procesos cognitivos) Facultad de Psicología Universidad Complutense de Madrid (2014)
Multidomain mild Cognitive Impairment (mMCI) patients have similar difficulties than those observed in the initial stages of Alzheimer disease. Many studies have explored language abilities in MCI, but few have focused in grammatical comprehension. This study explores the differences between mMCI patients and controls using a complete neuropsychological battery, it tries to discover if vocabulary and grammatical comprehension in both groups are predicted by naming and verbal fluency, and seeks the best subset of sentence structures to classify the subjects. There were significative differences between groups in verbs and in grammatical comprehension. Linear regression revealed that verb and sentence comprehension are independent of naming and verbal fluency performance in mMCI patients. In the control group verb comprehension is predicted by intrusions in verbal fluency, and the comprehension of sentences containing two propositions seems to be related to control processes and recognition errors. Two sentence structures, both not fitted to syntactic canonical order in Spanish, are especially useful for subjects’ classification. mMCI patients have a specific deficit affecting grammatical comprehension that doesn’t seem to depend on their low performance at lexical-semantic level. In healthy elders, verb and grammatical comprehension are related to control processes.